2015
DOI: 10.1007/s13312-015-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Methicillin-resistant Staphylococcus aureus infection in children

Abstract: Objective: To identify the clinical variables that differentiate MRSA (Methicillin-resistant Staphylococcus aureus) from MSSA (Methicillin-sensitive S. aureus) infection. Methods: Cases having culture isolates of Staphylococcus species were recruited. Baseline and other laboratory parameters were compared between MSSA and MRSA sub-groups to identify the predictors for MRSA. Results: Out of 98 isolates of S.aureus, 46 (47%) were MRSA. Significant leukocytosis was found in cases with MRSA (P <0.03). None of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…The median overall hospital stay was 10 days (IQR 6-17 days) for MRSA and 8 days (IQR 5-15 days) for MSSA; 14% (77/551) of infections required admission to PICU with stays of 8 days (IQR 6-11 days) for MRSA and 6 days (IQR 3-13 days) for MSSA. Of the total number of patients, 53% (41/77) received assisted ventilation with a median of 7 [4][5][6][7][8][9] days for MRSA and 9 [4][5][6][7][8][9][10][11] days for MSSA while inotropic agents were used in 77% (48/62) of the patients for 4 [3][4][5][6][7] days with MRSA and 6 2-9 days with MSSA. With respect to the number of days of hospitalization, a longer stay in hospital was only found in the group of MRSA OIs (P = 0.0006), and no significant differences were found in the number of days spent in the PICU.…”
Section: Resultsmentioning
confidence: 99%
“…The median overall hospital stay was 10 days (IQR 6-17 days) for MRSA and 8 days (IQR 5-15 days) for MSSA; 14% (77/551) of infections required admission to PICU with stays of 8 days (IQR 6-11 days) for MRSA and 6 days (IQR 3-13 days) for MSSA. Of the total number of patients, 53% (41/77) received assisted ventilation with a median of 7 [4][5][6][7][8][9] days for MRSA and 9 [4][5][6][7][8][9][10][11] days for MSSA while inotropic agents were used in 77% (48/62) of the patients for 4 [3][4][5][6][7] days with MRSA and 6 2-9 days with MSSA. With respect to the number of days of hospitalization, a longer stay in hospital was only found in the group of MRSA OIs (P = 0.0006), and no significant differences were found in the number of days spent in the PICU.…”
Section: Resultsmentioning
confidence: 99%
“…All of the 40 studies were considered for qualitative as well as the quantitative synthesis of etiological agents. Ultimately, only 34 of 40 studies were included in the MRSA meta-analysis, 8,9,15 -46 as the remaining 6 studies did not include data relevant to MRSA (4 efficacy studies, 1 study that described heteroresistance to vancomycin among methicillin-resistant S. aureus isolates, and 1 survey wherein no exact data on prevalence were presented). 47 -52 Table 1 represents the characteristics of the studies included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies 8,16,18,23,28,31,36,38,41,46 identified risk factors and co-morbidities, including diabetes, tuberculosis, malignancy, leprosy, extremes of age, group-house inhabitants, high mean body temperature (101.80°F), history of preceding illness/upper respiratory tract infections/trauma, abnormal laboratory values (hemoglobin [<9.5 g%], erythrocyte sedimentation rate [>35 mm/h], c-reactive protein [>32 mg/dL], leucocytes (>14 000 cells/10 9 L), absolute neutrophil count [(>65%]), immuno-compromised status, hospitalization in the last 3 months, present intake/history of antibiotics, history of surgical procedures, history of alcohol intake and smoking, history of intravenous drugs, history of corticosteroid intake, history of mucocutaneous candidiasis, history of dermatitis, history of sexually transmitted infections, socio-economic status, chronic kidney disease, heart disease, chronic obstructive pulmonary disease, rheumatoid arthritis, MRSA carriage (nasal or axillary or perineal or hand carriage in patients), prolonged duration of hospital stay, and irrational use/over prescription of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Impetigo was the most common bacterial infection similar to the published data[217] followed by Staphylococcal scalded skin syndrome (SSSS). Methicillin-resistant Staphylococcus aureus (MRSA) prevalence in children was 21.9% in a hospital-based Indian study,[19] which was seen in only two of our children (SSSS and Staphylococcal scarlatina). Fatality is reported in MRSA-induced SSSS,[20] stressing the importance to recognize and treat appropriately.…”
Section: Discussionmentioning
confidence: 92%